Patterns of verbal agreement with collective nouns taking plural of-dependents: a corpus-based analysis of syntactic distance. Issue 2 (August 2017) - Fernández-Pena, Yolanda
Abstract : In this study, I investigate the patterns of verbal agreement of twenty-three singular collective nouns in English which take plural of -dependents (e.g., a group of children or a bunch of people ). The main aim is to explore the extent to which this constituent may influence the number of the main verb, by considering factors such as the role of overt morphological markers for number in the oblique noun and the influence of syntactic distance on the patterns of verbal agreement. The data will show strong conditioning effects of the plural of -dependent on the verb, in triggering plural verbal number, for example. Contrary to what has been claimed hitherto, syntactic distance does not result in an increase of semantic (i.e., plural) agreement in this type of construction. In fact, the non-overtly marked plural noun people, whose influence on verbal agreement is strong in local syntactic domains, shows a considerable decrease in the proportion of plural verbal forms which it takes with increasing distance, contrary to overtly marked plural nouns. Finally, in light of the grammaticalisation suffered by homologous constructions such as a lot of, I will also consider the role of verbal agreement in the possible idiomatisation of the structures that I scrutinise here.